Answer:
y = 1/3(x + 5)^2 - 4
Step-by-step explanation:
The general vertex form is;
y = a(x-h)^2 + k
From the question, (h,k) are the coordinates of the vertex which is (-5,-4)
So we have
y = a(x + 5)^2 -4
So we need to get the leading coefficient
Simply substitute the point it passes through
x = -2 and y = -1
-1 = a(-2 + 5)^2 - 4
-1 = a(3)^2 -4
-1 = 9a -4
9a = 4-1
9a = 3
a = 3/9
a = 1/3
So the equation is;
y = 1/3(x + 5)^2 - 4
Answer:
-4 - 17x
Step-by-step explanation:
Anything enclosed in parentheses must be done first if possible. (3x + 2) is inside two sets of parentheses, but nothing can be done with 3x + 2.
Multiplication must be done next. [6(3x+2)-x] becomes 18x + 12 - x, or
17x + 12.
Now we have 4 - 17x - 12 + 4. Combining like terms through addition and subtraction, we get 4 - 12 + 4 - 17x, or -4 - 17x.
Answer:
a(b+c)= ab + ac
Step-by-step explanation:
The answer is D=3 11(3*+1)=4(3*+8)
11(4)=4(11)
44=44